Suicidal Behavior and Associations with Quality of Life among HIV-Infected Patients in Ibadan, Nigeria. (July 2017) - Oladeji, Bibilola Damilola; Taiwo, Babafemi; Mosuro, Olushola; Fayemiwo, Samuel A.; Abiona, Taiwo; Fought, Angela J.; Robertson, Kevin; Ogunniyi, Adesola; Adewole, Isaac F.
Background: Suicidality has rarely been studied in HIV-infected patients in sub-Saharan Africa. This study explored suicidal behavior in a clinic sample of people living with HIV, in Nigeria. Methods: Consecutive patients were interviewed using the Composite International Diagnostic Interview (CIDI-10.0) and the World Health Organization Quality of Life (WHO-QOL-HIV-BREF). Associations of suicidal behavior were explored using logistic regression models. Results: In this sample of 828 patients (71% female, mean age 41.3 ± 10 years), prevalence of suicidal behaviors were 15.1%, 5.8%, and 3.9% for suicidal ideation, plans, and attempts, respectively. Women were more likely than men to report suicidal ideation (odds ratio 1.7; 95% confidence interval 1.05-2.64). Depression and/or anxiety disorder was associated with increased odds of all suicidal behaviors. Suicidal behavior was associated with significantly lower overall and domain scores on the WHO-QOL. Conclusion: Suicidal behaviors were common and significantly associated with the presence of mental disorders and lower quality of life.